Pre-pleistocene palaeo-relief investigation of the Levidi basin (Peloponnesus, Greece) based on geophysical investigation - Alexopoulos, J. (Bulletin of the Geological Society of Greece, 2008)
The closed intra-mountainous Levidi basin (average altitude 680 m), characterized by an asymmetric spatial extension, drains at its south-eastern part by the homonymous sinkhole, and its paleorelief is covered by homogeneous quaternary sediments. The boundaries of the basin consist mostly of carbonate and clastic sediments of the Pindos unit, while carbonate sediments of the Tripoli unit are limited to the south and south-western parts. In order to investigate the alpine basement of the quaternary deposits, the geometry of the prequaternary topography of the basin and the lithology of the quaternary sediments, geophysical investigation was employed. The study involved 27 geoelectrical soundings and 7 resistivity measurements, both in boreholes and surface outcrops of the alpine formations. The results of the geophysical investigations facilitated the constructing of (i) the sub-terrain morphological map of the alpine basement, where the thickness of Pleistocene sediments in the central part of the basin does not exceed 15 m, although in the area of Palaeopyrgos (to the north-east) the sediments appear to reach a thickness up to 60 m, and (ii) the sub-terrain geological map. Structurally, the Levidi basin can be characterised as a polje, formed as a result of alpine deformation and subsequent karsting, accentuated by the lack of impermeable flyschic formations in the area.